Sources of Technological Innovation in Brazilian Agriculture - International Service for National Agricultural Research (International Service for National Agricultural Research, 1999)
Most studies on technological innovation in agriculture tend to focus on public agricultural research only. They largely ignore the fact that a substantial part of the technology used in agriculture is being acquired by buying inputs from various industries or by means of technology contracts and spillovers. The acquisition of technology through purchased inputs has been the subject of a recent OECD study (OECD 1996a), which provides very useful and interesting insights into the technological interdependency between industries and countries. The study uses input-output matrix data to trace transfers of technology embodied in inputs from one industry to another. In this paper we will apply an adapted version of this approach to the Brazilian agricultural sector as to improve our understanding of the contribution of the various sources of technological innovation to Brazilian agriculture.